From Bonds to Brains: Understanding the Impact of Attachment on Executive Functions in Adolescents - María Sancho; María J. Luque-Rojas; Carlos Pitillas (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
Introduction: This study explores the critical relationship between attachment styles and executive functions in adolescents, focusing on how secure, ambivalent, and avoidant attachment styles affect core cognitive functions such as emotional regulation, planning, and cognitive flexibility. Method: This study used a cross-sectional design to assess 283 adolescents aged 13-17 from various schools in Spain. Attachment styles were evaluated using the CaMir-R questionnaire, while executive functions were measured through the BRIEF-SR. Statistical analyses, including Mann-Whitney U and Student’s t-tests, were used to compare cognitive performance across secure and insecure attachment groups. Results: The analysis revealed that adolescents with secure attachment demonstrated significantly better overall cognitive performance compared to those with insecure attachment (U = 7569.5, p .01), as well as in most of the subcomponents, which included cognitive flexibility, emotional regulation, and planning/organization. However, no significant differences were found in inhibitory control between the groups. Insecure-avoidant individuals exhibited greater difficulties overall than insecure-ambivalent individuals in all subcomponents studied. Conclusion: The results reinforce the link established between secure attachment and superior cognitive performance, aligning with previous research on emotional regulation and cognitive development in adolescence. However, the absence of significant differences in inhibitory control suggests that this executive function may be influenced by additional factors beyond attachment, such as environmental or contextual variables. Furthermore, the finding that insecure-avoidant individuals exhibit greater executive function difficulties than insecure-ambivalent individuals highlights the need to further investigate how different insecure attachment patterns impact cognitive processes. These insights have important implications for educational practices, suggesting the need for targeted interventions to support adolescents with insecure attachment, particularly those with avoidant tendencies.